Marzec 68’ w polskim kinie – o "Różyczce" Jana Kidawy-Błońskiego - Bałdyga, Katarzyna (Załącznik Kulturoznawczy, 2023)
The article refers to March events in Polish cinema. Little Rose, film by Jan Kidawa-Błoński, becomes the main material of the analysis. The first part of the article relates to two documentary films by Maria ZmarzKoczanowicz which help to interpret many key scenes in the film of KidawaBłoński. Gdanski Railway Station sheds some light on the final scene of the Little Rose. It also shows how dramatically March events affected the privacy of Polish people. An Ordinary March presents the struggle of Polish intelligentsia with the system – so it demonstrates what is official. Little Roseconnects both perspectives – it shows the history from the point of view of ordinary people, as well as it doesn’t resign from presenting well-known and concluded in historical syntheses issues